Exploratory Factor Analysis MSMEs Anti-Fragile - Fauji, Diah Ayu Septi; Pratikto, Heri; Handayati, Puji (International Journal of Science, Technology & Management, 2022)
Developing a framework for MSMEs to become more fragile is the goal of this research. As it is known that the business world has fluctuated a lot and is facing turbulence, so we need an anti-fragile MSME framework concept. Using Exploratory Factor Analysis (EFA), this research is then analyzed to produce 5 (five) factors that build an anti-fragile MSME framework, namely Network Building, Growth Mindset, and Willingness to Develop, Focusing on Sustainability, Support, and Ability to Overcome Risk and the last is Competence. So far, there has been no research on the anti-fragile concept for MSMEs in Indonesia, so it is hoped that the results of this study can be a reference for future researchers and business actors in running their businesses.